Playing the game by the rules? - Guo, Zhenzhi (Javnost (Ljubljana), 2003)
China's entry into the World Trade Organization (WTO) heated up discussions onthe importance and urgency of regulatory reform in Chinese television. Entering the WTO means, first and foremost, situating China in a legal framework that is communicative, negotiable and operational within international (primarily Western) standards. For Chinese media, such reform suggests an important move on part of the Chinese government from traditional political control to legal regulation. This paper reviews the development of television regulations in China in the reform era. It begins with a brief introduction to a few Chinese key words, Fa Zhi (law) and Gui Zhi (regulation), against the background of China's legal reforms. It then proceeds to show the development of Chinese broadcasting regulations in a changed industrial environment. Next, it examines regulations of Chinese television, focusing on organizational restructuring and program disciplining.The paper concludes with a brief discussion of the prospects and problems of regulatory reform, especially within the context of globalization. Far from most optimistic predictions, this paper argues that to date regulatory changes in Chinese television are more restrictive than liberalising; and that transformation of China's television from administrative control to lawful regulation still has a long way to go.
Keywords: Kitajska; television; televizija; država; state; nadzor; cenzura; demokratizacija